Heparinized saline versus normal saline for maintaining peripheral venous catheter patency in China: An open-label, randomized controlled study. (April 2017) - Xu, Lichun; Hu, Yan; Huang, Xiaojin; Fu, Jianguo; Zhang, Jinhui
Objective: To evaluate the effects of heparin saline versus normal saline as locking solution for maintaining patency in peripheral venous catheters in Chinese patients. Methods: This open-label, randomized controlled study was conducted in two hepatobiliary surgery wards, where patients received identical treatments, at a tertiary referral hospital. Patients were randomly divided into a normal saline group (NS, 3 ml) or a heparin saline group (HS, 50 IU/ml, 3 ml) for catheter sealing. Results: The study enrolled 286 patients and 609 peripheral venous catheters were included in the analysis. The patients in the two groups had no local infections or catheter-related bloodstream infections. There were no significant differences between the two groups in terms of the rate of catheter obstruction, duration time, or the rates of phlebitis, infiltration, and accidental catheter removal. Conclusions: No significant differences in the peripheral venous catheter sealing effects were observed between normal saline and heparin saline usage in Chinese patients.